107P Increasing responses to T-cell therapies in solid tumours by the use of an engineered adenovirus coding for TNFa and IL-2. (15th December 2019) - Cervera-Carrascon, V; Havunen, R; Santos, J M; Quixabeira, D C A; Hemminki, A; Zafar, S
Abstract: Background: During the last decade, a revived enthusiasm about T-cell related therapies emerged after promising clinical outcomes. Nevertheless, many patients (especially with solid tumours) still do not have adequate therapeutic options. The complexity of the tumour microenvironment is a likely factor acting in detriment of many of those therapies by multiple suppressive mechanisms. To tackle a complex mechanism, an oncolytic adenovirus 2 (Ad5/3-E2F-d24-hTNFa-IRES-hIL2, a.k.a. TILT-123) was engineered to enable T-cell therapies in those circumstances. Methods: To study the efficacy of TILT-123 together with different T-cell related therapies (adoptive cell transfer, checkpoint inhibitors and CAR T cell therapy) different models were used including mouse, Syrian Hamster and patient derived in vivo models for different indications were tested. Results: Antitumor efficacy analyses showed complete responses in all animals receiving a T-cell therapy or checkpoint inihibitor (aPD1 or aPDL-1) and the T-cell enabling virus. Further, other aspects such as safety, influence on different immune populations, abscopal effect, antitumor memory and ability to replace lympho-depleting chemotherapy and postconditioning with high-dose IL-2 treatment were studied. Conclusion: The use of TILT-123 to enable T-cell therapies (including checkpoint-inhibiting antibodies) delivered encouraging preclinical results pointing to it as a valuable approach to increase the number of patients that benefit from T-cell therapies. Those results include not only cell based therapies but also checkpoint inhibitors, a kind of therapy that is making the difference in the field and becoming first-line treatment for an increasing number of indications. Because of the favourable preclinical studies, the first in human clinical trials with TILT-123 will start in the upcoming months. Legal entity responsible for the study: The authors. Funding: TILT Biotherapeutics. Disclosure: V. Cervera-Carrascon: Full / Part-time employment: TILT Biotherapeutics. R. Havunen: Full / Part-time employment: TILT Biotherapeutics. J.M. Santos: Full / Part-time employment: TILT Biotherapeutics. A. Hemminki: Shareholder / Stockholder / Stock options, Full / Part-time employment, Officer / Board of Directors: TILT Biotherapeutics. All other authors have declared no conflicts of interest.